Biopetrol synthesized from palmitic acid-heterogeneous catalytic cracking by granular metal - Mohd Hidayat, Hashim (2010)
Palmitic acid is one of the major fatty acid in vegetable oil.In this research,granular copper catalysts are used over the conversion of palmitic acid into isooctane as the future biopetrol.Biopetrol is defined as fuel which has the same characteristics with commercial petrol in terms of its molecular formula.The main purposed of studies is to improve the concentration of isooctane using dynamic catalytic cracking method.The effect of various rotation speeds of agitator at 600rpm, 780rpm, 960rpm and 1120rpm are studied over the yield of biopetrol at 98oC.Gas chromatography is used for the qualitative and quantitative analysis of the samples.Backward calculation is applied to calculate the actual concentration of isooctane in the diluted cracking palmitic acid.The maximum yield of desired isooctane obtained at 960rpm of rotation speed is recorded at 27.09555%.Experimental works has successful show that dynamic catalytic cracking is greater in conversion than static catalytic cracking and thermal cracking